Social work with African American males health, mental health, and social policy - Johnson, Waldo E. (Waldo Emerson), 1955- (New York ; Oxford : Oxford University Press, 2010)
Stepping back from the traditionally myopic view of African American males as criminals and hustlers, this book provides a more nuanced and realistic portrait of their experiences in the world, offering an overview of the social and economic data on black males to date and the issues that affect them from adolescence to adulthood.
Description based on print version record.
Includes bibliographical references and index.
Keywords: African American men -- Services for; Social work with African Americans; African American men -- Social conditions